Cheret X Lautrec: tradição e modernidade na arte do cartaz. - Silva, José Marcos Romão da [UNESP] (My University, 2011)
Through the comparison between the work circus advertisements of Jules Cheret and Toulouse Lautrec, is it possible to trace a suggestive panorama of the clash that gave at the end of the 19TH century. 19TH CENTURY between the academic tradition and the innovations of modern art. Results from a combination of elements very characteristic, such as the brevity of the design associated with the use of flat areas of contrasting colors and words in italic in different types, the poster will be the most effective and popular means iconic-graph in this period, taking to assault the streets of major cities.

Através da comparação entre a obra cartazística de Jules Chéret e Toulouse Lautrec, é possível traçar um sugestivo panorama do embate que se deu no final do séc. XIX entre a tradição acadêmica e as inovações próprias da arte moderna. Resultado da combinação de elementos muito característicos, como a concisão do desenho associado ao uso de áreas planas de cores contrastantes e palavras grafadas em diferentes tipos, o cartaz irá se constituir no mais eficaz e popular meio icônico-gráfico nesse período, tomando de assalto às ruas das grandes cidades.
Keywords: Poster; Lithography; Modern art; Cartaz; Litografia; Modernidade